PENGARUH PUPUK MAJEMUK NPKMg DAN PUPUK ORGANIK SUPER K PADA PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Setiawan, M. Guna; Khoiri, M. Amrul; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Â 1This study aims to determine the effect of applying NPKMg compound fertilizer and super K organic fertilizer and to get the best combination for the growth of oil palm seedlings in the main nursery, which was held from October 2020 to April 2021 in Sekijang Village, Tapung Hilir District, Kampar Regency. This research was conducted experimentally using a factorial Completely Randomized Design (CRD). The first factor is NPKMg compound fertilizer with 2 levels, namely A1: 7.5 g per polybag, A2: 10 g per polybag. The second factor is super K organic fertilizer with 3 levels, namely O1 : 6.25 g per polybag, O2 : 12.5 g per polybag, O3 : 18.75 g per polybag. Parameters observed were hump circumference, root wet weight, root dry weight, canopy wet weight, and canopy dry weight. The data obtained were analyzed statistically using analysis of variance and further tested with Duncan's multiple distance test at a level of 5% using the SPSS application. The results showed that the application of 10 g NPKMg compound fertilizer per polybag was able to increase the growth of oil palm seedlings in the main nursery. The application of super K organic fertilizer at the level of 12.5 g per polybag was able to increase the growth of oil palm seedlings. The combination of NPKMg compound fertilizer with a level of 10 g per polybag and organic super K fertilizer with a level of 12.5 g per polybag gave the best results for the growth of oil palm seedlings.Â Keywords:NPKMg compound fertilizer,organic super K fertilizer, oil palm seedlings